PEMBELAJARAN TARI KREASI BARU DALAM KEGIATAN EKSTRAKURIKULER SISWA SMP NEGERI 22 PALEMBANG - Aisyah Ramadhanti; Deria Sepdwiko; Efita Elvandari (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to describe the implementation of new creative dance learning in extracurricular activities and its impact on students’ creativity at SMP Negeri 22 Palembang. The research employed a qualitative approach with a descriptive method. Data collection techniques included observation, interviews, and documentation. The research subjects consisted of dance extracurricular instructors and students participating in dance extracurricular activities. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that the learning process of new creative dance was carried out systematically through planning, implementation, and evaluation stages. The learning activities were conducted using demonstration methods, direct practice, movement exploration, and group work. Students showed enthusiasm and active participation during the learning process. New creative dance learning had a positive impact on improving students’ creativity, self-confidence, teamwork skills, and kinesthetic intelligence. However, several obstacles were found, such as limited practice time, inadequate facilities, and differences in students’ abilities. Therefore, new creative dance learning in extracurricular activities can be considered effective as a means of developing students’ overall potential.